Mitochondrial Fission as a Therapeutic Target for Metabolic Diseases: Insights into Antioxidant Strategies - Tianzheng Yu; Li Wang; Lei Zhang; Patricia A. Deuster (MDPI AG, 2023)
Mitochondrial fission is a crucial process in maintaining metabolic homeostasis in normal physiology and under conditions of stress. Its dysregulation has been associated with several metabolic diseases, including, but not limited to, obesity, type 2 diabetes (T2DM), and cardiovascular diseases. Reactive oxygen species (ROS) serve a vital role in the genesis of these conditions, and mitochondria are both the main sites of ROS production and the primary targets of ROS. In this review, we explore the physiological and pathological roles of mitochondrial fission, its regulation by dynamin-related protein 1 (Drp1), and the interplay between ROS and mitochondria in health and metabolic diseases. We also discuss the potential therapeutic strategies of targeting mitochondrial fission through antioxidant treatments for ROS-induced conditions, including the effects of lifestyle interventions, dietary supplements, and chemicals, such as mitochondrial division inhibitor-1 (Mdivi-1) and other mitochondrial fission inhibitors, as well as certain commonly used drugs for metabolic diseases. This review highlights the importance of understanding the role of mitochondrial fission in health and metabolic diseases, and the potential of targeting mitochondrial fission as a therapeutic approach to protecting against these conditions.